Systems and Innovation Research in Transition Research Questions and Trends in Historical Perspective - Edler, Jakob; Walz, Rainer; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This open access volume reflects on the research fields that have developed in the last five decades in the area of Systems and Innovation Research (SIR). It presents a systematic history of nine selected fields within the area of SIR. We also present a conceptual framework to understand the processes by which the research fields have developed. This allows to draw general lessons as to what drives research fields throughout their development and how their role vis-a-vis policy, businesses and societies changes over time. This is important because, if anything, the need to govern transformation through innovation will further grow in the future, and with it the need to understand the underlying systems and innovation dynamics.
Introduction -- Understanding paradigm change in science, technology and innovation policy: Between science push and policy pull -- Development of innovation monitoring and innovation indicators in the past 50 years -- Foresight. Fifty years to think your futures -- Evaluating public research and innovation policies. A short history of co-evolution -- Assessing technological innovations. From early warning to the governance of socio-technical transformations -- Industry in a changing era. Production paradigms during the last 50 years -- From Niche to Mainstream: Exploring innovation and progress of renewable energy development -- Energy Demand and Modelling of Energy Systems. Five Decades from Little Knowledge to Differentiated Know-how -- Understanding the co-evolution of research and water protection policies: from single technologies to systemic integrated approaches for the sustainable use of water -- Drivers and patterns of change in systems and innovation research.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Technological innovations; Sustainability; Innovation and Technology Management; Sustainability; Economics of Innovation